Factors Affecting Satisfaction of Receiving Procurement Services of Construction Business Group in Southern Thailand - Kwansuksri , Pakkaporn; Nagamatsu, Maneekanya (Journal of Modern Learning Development, 2023)
The objectives of this research were 1) to study procurement management and satisfaction of employees. 2) To compare satisfaction factors of employees towards the procurement services distinguish the personal factors, and 3) to study relation between procurement management and satisfaction factors of employees towards the procurement services. The sample size was 248 personals using Krejcie & Morgan table. The statistical were frequency, percentage, mean, standard deviation, t-test, one-way ANOVA, and multiple regression analysis. The results showed that 1) the employee of the construction business group had satisfaction to procurement services at the highest level. 2) the demographic factor; the difference education and department factors did different significant satisfaction to procurement services at 0.05 level. And 3) the appropriate quality aspect and appropriate accurate factors had relation significantly satisfaction to procurement services overall and appropriate price and accuracy required aspect at 0.05 level. The appropriate quality factor had relation significantly satisfaction to procurement services on appropriate quality aspects at 0.05 level. And the appropriate quality and scheduled delivery factors had relation significant satisfaction to procurement services on scheduled delivery aspects at 0.05 level.